A Systematic Literature Review Information Technology Sophistication: Capital and Performance - Ady Putra Sinambela; Sambas Ade Kesuma; Iskandar Muda (International Journal of Social Service and Research (IJSSR), 2023)
This Systematic Literature Review aims to conduct a literature review in the field of technological sophistication with data from all international research publications in the field of accounting information systems. The relevant data in this review were obtained from 50 articles from 1994 to 2022 globally. The results of research in many articles that discuss the relationship of information technology in improving company performance, various results methods describe the relationship between Information Technology business and strategic alignment. So that in this alignment strategy emerges important attention to the views by business and IT (Information Technology) executives around the world (Raymond and Coretau, 2009, Johnson and Lederer, 2010). The purpose of this article is to add a detailed literature review so that it can be used by academics and practitioners in understanding the resources needed to maximize technological sophistication. This can be obtained by exposing information technology literature related to company performance. It is hoped that this article will be useful for ongoing discussions regarding sophistication of technology in companies.